Franz Joseph Gall on the Cerebellum as the Organ for the Reproductive Drive - Eling, Paul; Finger, Stanley (Frontiers in Neuroanatomy, 2019)
Franz Joseph Gall (1758-1828) is best remembered for his belief that bumps on the skull reflect the growth of small, underlying brain areas, though among some historians more positively for introducing the concept of cortical localization of function. All but one of Gall's 27 settled-upon cortical faculties involved the cerebral cortex, the exception being his most primitive faculty, reproductive instinct, which he associated with the cerebellar cortex. This article examines Gall's earlier subcortical organs, with an emphasis on why he associated the cerebellum with this drive. It draws from accounts by several physicians, who attended his Vienna lectures or heard him speak in Germany and the Netherlands in 1805-1806 (i.e., before he published his finalized list in his Anatomie et Physiologie (1810-19). These early accounts show that early on he localized at least four faculties in brainstem structures, including reproductive drive in the cerebellar cortex. He based his structure-function association primarily on cranial differences between men and women, and what he found in males and females of other species, although cranioscopy was not his sole method. It is also shown that, in opposition to his cerebellar-reproductive drive association, Marie Jean Pierre Flourens linked coordinated skeletal movements to the cerebellum after conducting lesion experiments, mainly on birds. Flourens did not design his experiments to challenge Gall’s ideas on localization of function but they did just that. Gall responded that ablation methods lack precision and lead to misguided conclusions. How Gall continued to associate the reproductive instinct with the cerebellar cortex, even after deleting his other brainstem-based associations from his faculties of mind, tells us much about him and the faith he had in his methods and doctrine.